Algoritma K-Means untuk Mengelompokkan Hotel di Sekitar Wilayah Indonesia yang Rentan Gempa Bumi - Nurfidah Dwitiyanti; Erlin Windia Ambarsari; Noni Selvia (STMIK Budi Darma, 2023)
Due to its location on the Pacific Ring of Fire, Indonesia frequently experiences earthquakes. This phenomenon endangers society and infrastructure, including the hotel industry. Hotels are placed based on locations around areas of Indonesia vulnerable to earthquakes so that hotel owners can use hotel designs and construction that are earthquake-resistant when built. This is because areas with high earthquakes increase the risk of damage to hotel buildings. This research uses hotel geographic location data and Indonesian seismic data to classify hotels in earthquake-prone regions of Indonesia using the K-Means algorithm. Data was taken from USGS from January 2022 to November 2023. Using the K-Means algorithm, hotels were aggregated into clusters based on their proximity to the earthquake epicenter and recorded earthquake magnitude. The research results show that there are two ideal clusters based on the highest Shilhoutte value, namely 0.954, which means it can be sent into two different clusters based on latitude, longitude, and hotel address, with four hotels and three hotels as members of each cluster. Hotels Mutiara, Saparua, and Tiara have a higher level of vulnerability than other hotels because they are located near the earthquake. This research can help hotel owners and policymakers create strategies to reduce risk, increase safety, and develop sustainability in earthquake-prone regions.